Pengembangan E-Book Informatika Berbasis Canva pada Materi TIK Kelas X di SMA Negeri 5 Samarinda - Muhammad Rizal Nur Wahid; Galih Yudha Saputra; Eko Subastian (Morfologi : Jurnal Ilmu Pendidikan, Bahasa, Sastra dan Budaya, 2025)
Development of a Canva-Based Informatics E-book on ICT Material for Grade X at SMA Negeri 5 Samarinda. This research aims to determine the feasibility of a product in the form of an E-book as a learning medium and to assess the response toward the Canva-based Informatics E-book for Grade X students at SMA Negeri 5 Samarinda. This study employs a Research and Development (R&D) method with the PPE model, which consists of three stages: Planning, Production, and Evaluation. The research subjects involved 35 students from Grade X (I) at SMA Negeri 5 Samarinda, along with 3 media experts and 1 material expert. The research object is the Canva-based Informatics E-book on ICT material. The results showed that the development of the Canva-based E-book, as evaluated by 3 media expert validators, obtained a percentage score of 92.19%, which falls into the “Highly Feasible” category. The Evaluation conducted by 1 material expert achieved a percentage score of 100%, also in the “Highly Feasible” category. Furthermore, students’ responses to the product were measured and obtained an average percentage score of 82.57%, which falls into the “Very Interesting” category. Thus, the development of the Canva-based E-book on ICT material for Grade X at SMA Negeri 5 Samarinda, developed using the PPE model, is declared highly feasible based on media and material expert validation and very interesting based on students’ responses.